Assessing Climate Change Effects on Mahseer Growth Properties - Iskandar Nur Syuhada; Md Noor Noorashikin; Che Cob Zaidi; Das Simon Kumar (E3S Web of Conferences)
Heatwaves are becoming more common and severe due to rising CO2 and temperature levels, while changes in precipitation patterns have significant consequences for ecosystems and aquatic creatures, including fish. This study assessed the growth parameters of the valuable mahseer, a key species in fisheries and ecological balance, under different temperature and CO2 concentration conditions: (26°C + 400 ppm CO2), (34°C + 400 ppm CO2), (26°C + 600 ppm CO2), and (34°C + 600 ppm CO2). The experimental setup included controlled aquaria where mahseer were reared for a specified period. Growth parameters such as body weight gain (BWG) and specific growth rate (SGR) were measured and analyzed using appropriate statistical methods. The results showed that the highest growth parameters, including BWG and SGR, were observed in mahseer reared at 26°C with 400 ppm CO2. Conversely, the lowest growth parameters were recorded in mahseer raised at 34°C with 600 ppm CO2. These findings indicate that moderate temperatures and lower CO2 levels provide optimal conditions for mahseer growth, while elevated temperatures and higher CO2 concentrations, conditions expected to become more prevalent with ongoing climate change, negatively impact their growth. This preliminary study provides a foundation for future research on mahseer rearing in a changing climate, emphasizing the need to maintain favorable environmental conditions and develop strategies to mitigate the adverse effects on this valuable species. Further investigations should include more extensive sampling, varied environmental parameters, and long-term studies to fully understand the implications of climate change on mahseer and other aquatic organisms.